Pengaruh Supervisi Akademik Pembelajaran Pengawas Madrasah Terhadap Kinerja Guru Min Kota Jayapura - Sutinah Sutinah (Jurnal Pendidikan Indonesia, 2022)
Education is at the core of a nation's progress. However, in reality, it is only rhetorical even though it has been 77 years of independence. The low professionalism of teachers in Indonesia can be seen from the feasibility of teaching. One of the efforts to improve teacher professionalism is carried out through academic supervision of madrasah / school supervisors in supervising teacher performance. For this reason, the role of learning academic supervision carried out by madrasah/school supervisors is very influential in order to improve teacher performance in teaching. This research was conducted on teachers at MIN Jayapura City totaling 9 civil servant teachers who were considered advanced supervisors. The research conducted is a Supervisory action research in which the approach used in this research is a quantitative descriptive approach. The implementation of academic supervision of madrasah/school supervisors' learning affects the performance of MIN teachers in Jayapura City. The performance of MIN teachers increased from the category of poor scores (≤ 50) to very good (≥ 86).